PolyQ Length of the Clock Gene Is Correlated With Pelagic Larval Duration in the Damselfishes (Pomacentridae), but Within a Species Habitat Availability Counts - Gregor Schalm; Simon Kaefer; Philipp Krämer; Anna‐Lena Jäger; Michael J. Kingsford; Gabriele Gerlach (Ecology and Evolution, 2025)
ABSTRACT Immediately after hatching, larvae of coral reef fish leave their natal reef environment and begin their pelagic larval phase probably to avoid high predation on the reef. The time they spend in the open ocean (pelagic larval duration, PLD), before settlement varies from species to species and depends partly on developmental processes that eventually require re‐settlement to a reef. The polyglutamine region (PolyQ) as part of the clock gene has been suggested as a possible candidate that could control developmental processes and potentially the time until settlement, which can be determined by counting the rings of the otoliths. We studied the potential relationship between the number of glutamine repeats in 20 species of pomacentrids and their PLDs. Most pomacentrids came from similar locations, so we avoided the impact of latitudinal clines on PLD. Within the clock gene, we found two main distinguishable, variable glutamine‐rich regions (PolyQ and Qrich). Considering phylogenetic relationships, PolyQ/Qrich repeat length and pelagic larval duration were significantly positively correlated. However, when analyzing this relationship in a single species, the neon damselfish (Pomacentrus coelestis), we did not find a significant correlation between PolyQ length variation and PLD. Instead, we found a significant reduction of PLD in years with increased habitat availability. Our results show that glutamine‐rich regions can influence the timing of settlement on a broader scale, but that ecological factors—such as habitat availability—can also have a significant impact.